Trends and spatial distribution of Human African Trypanosomiasis (HAT), Uganda, 2005 – 2015: A descriptive analysis of surveillance data - Susan Kizito; Charles W. Wamboga; Edridah Muheki Tukahebwa; Abbass Kakembo; Lilian Bulage; Alex Riolexus Ario (Journal of Interventional Epidemiology and Public Health)
Background: Human African Trypanosomiasis (HAT), commonly referred to as sleeping sickness, is a neglected tropical disease endemic in Sub-Saharan Africa. It is caused by Trypanosoma brucei (T.b.) sub-species: rhodesiense (Rhodesian HAT) and gambiense (Gambian HAT) parasites. The World Health Organization (WHO) targeted HAT for elimination as a public health problem by 2020 (annual incidence ≤1/10,000, and early diagnosis for all cases). We evaluated progress towards HAT elimination in Uganda and described its epidemiological characteristics. Methods: We analysed data reported from sleeping sickness treatment centres (SSTCs) to the Uganda National Sleeping Sickness Control Program during 2005–2015. A HAT case was defined as identification of T.b. rhodesiense or T.b. gambiense parasites in the blood (early-stage) or cerebrospinal fluid (late-stage) of patients at a SSTC. We analysed the cases’ distribution by person, time, and place. We used projected population data from 2002 and 2014 censuses, and linear regression to evaluate temporal trends. Results: During 2005–2015, SSTCs reported 2,032 HAT cases, (55% Rhodesian and 45% Gambian). The number of districts reporting AT reduced from 18 in 2005 to three districts in 2015. The average annual incidence rate (/10,000) during 2005–2015 was similar between males (Gambian=0.1, Rhodesian=0.76) and females (Gambian=0.09, Rhodesian=0.74). Gambian AT incidence declined annually by 24% (IRR=0.76; CI: 0.74-0.78) while Rhodesian AT declined annually by 13% (IRR=0.87; CI: 0.85-0.89). However, for both diseases more than 50% of cases were diagnosed in the late stage. Conclusion: Uganda has achieved the WHO 2020 elimination target for AT incidence. However, many cases are still diagnosed late. We recommend sustaining efforts to achieve eradication, emphasising early case detection and diagnosis and follow up of all AT cases to ensure good treatment success.